INTEGRATING SERVICE LEARNING FOR CATECHIST FORMATION AT PASTORAL COLLEGE IN MALANG, INDONESIA - Emmeria Tarihoran; FX. Eko Armada Riyanto; Antonius Denny Firmanto (Sanata Dharma University Yogyakarta, 2026)
This article examines the implementation of service learning in theological education to foster theological and transform students' Faith. The primary objective of this research is to explore how service learning can enhance students' understanding of theology while promoting their spiritual and social development. A case study approach was employed at the Pastoral College-IPI Malang, where data was collected through in-depth interviews and participatory observations. The findings indicate that service learning significantly influences students' character, spirituality, and social competence. Students reported a deeper theological understanding, a strengthened commitment to their Faith, and the practical application of Christian values in their daily lives. This study highlights the benefits of integrating service learning into theological education, demonstrating its effectiveness in empowering students' Faith and facilitating their transformation in alignment with their Christian calling. Ultimately, the research underscores the importance of service learning in preparing students to become dedicated servants in society.